Clinical evaluation of the installation conditions and accuracy of wearable neonatal jaundice meter - Azusa Uozumi; Ibuki Ohara; Masaki Shimamura; Kazuhiro Iwama; Ayako Fukuyama; Haruko Horiguchi; Yutaka Isoda; Fumiya Kimura; Hiroki Ota; Shuichi Ito (Scientific Reports)
Abstract Neonatal jaundice is a physiological phenomenon that occurs in newborns. However, because excess bilirubin can cause cytotoxicity, abnormal hyperbilirubinemia can lead to bilirubin encephalopathy. In the evaluation of neonatal jaundice, serum bilirubin concentrations are indirectly assessed via a transcutaneous bilirubinometer. However, commercially available transcutaneous bilirubinometers are expensive, especially in developing countries. Therefore, many newborns still suffer from bilirubin encephalopathy worldwide. We previously developed a prototype wearable jaundice meter. In this study, we aimed to investigate further improvements in this device and evaluate its measurement accuracy at different measurement sites and at different pressures. The bilirubin values of forty-eight newborns were measured at different sites (middle of the forehead and upper eyebrows) and with different pressures (1 and 2 newtons). The transcutaneous bilirubin values measured by the wearable bilirubin meter were strongly correlated with the transcutaneous bilirubin values measured by a commercially available bilirubin meter (r > 0.9) and the actual serum bilirubin values (> 0.84), even under different conditions. This wearable jaundice meter is much cheaper and smaller than commercially available jaundice meters and is a novel medical device that could be useful for evaluating neonatal jaundice.